PENGARUH SIKAP, KEBUTUHAN BERPRESTASI DAN EFIKASI DIRI TERHADAP INTENSI BERWIRAUSAHA - Akhmad Nurrofi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
ndonesia is a country whose population is increasing, so theunemployment rate is increasing due to the narrowness of employment. Thecurrent number of workers exceeds the number of employment fulfillment.This study aims to analyze the intensity of entrepreneurship as an alternativein overcoming employment problems. The data of this research wereconducted by questionnaire. The sample used in this study were 100respondents and sampling from population using census technique Thepopulation in this study is STIE Totalwin Semarang class students whohave received entrepreneurship courses. Hypothesis testing in this study usingmultiple regression analysis. The result of research with multiple linearregression shows that attitude, achievement requirement, self efficacyhavepositive and significant influence to entrepreneurship intention.